"God Bless Texas. God Bless the NRA": Problematizing Texas Teachers as Armed Protectors in the Aftermath of Sandy Hook. (April 2017) - Pérez, Michelle Salazar
The shooting at Sandy Hook elementary and other past and more recent acts of school violence involving guns in the United States have created considerable national dialogue about how we can prevent such horrific acts from happening in the future. In Texas, public conversation has ensued about the possibility of arming teachers, school staff, and administrators to "protect" and "defend" schools from similar attacks. Media discourses produced by the general public, right-wing political leaders, and organizations like the National Rifle Association (NRA) have been instrumental in advocating for teachers and other school personnel to become armed protectors. As such, in this article, I describe the context of the debate to arm Texas teachers as portrayed by newspaper outlets across the state while problematizing the dominant discourses they produce.